Organizational Vigor Creation Paradigm Model in Universities - Behnoush Jovari (International Journal of Management, Accounting and Economics, 2023)
This study aimed to identify and validate the organizational vigor creation model in the universities. In order to identify factors affecting the organizational vigor, after a focused literature review the consensus of the experts' opinion was explored. This information was placed in the form of a set of causal, intervening, axial, underlying, facilitating, strategic conditions and their outcomes by multiple codings based on granded theory model. These data were collected from 169 experts by snowball sampling method and the hypotheses were tested. For checking validity and reliability of the designed model SmartPLS and Spss softwares were used. Finally the relationships of these variables were presented based on the path analysis model. Based on the obtained results, Organizational vigor creation model, university growth has a significant effect on the strategic management of human resources; also, strategic management of human resources, intervening conditions and organizational support in resolving work-family conflict have a significant effect on university branding, and the latter also has a positive and significant effect on the vigorous state of human resources of the universities. The results of fitting showed that the model proposed in this study has good validity and fit. The significance, implications and limitations of results have also been deliberated for further research.